2022
DOI: 10.22270/jddt.v12i3-s.5356
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antibacterial activity of Fosfomycin and Nitrofurantoin against Pseudomonas aeruginosa and Acinetobacter baumannii against clinical isolates collected from Indian tertiary care hospitals

Abstract: The remarkable increase in resistance to currently available antibiotics to Gram-negative pathogens particularly multidrug resistant (MDR) Pseudomonas aeruginosa and Acinetobacter baumannii, This has resulted in increasing use of older under evaluated antibiotics such as fosfomycin, nitrofurantoin,  and Trimethoprime-Sulfamethoxazole for the treatment of infections caused by MDR pathogens. However, limited in-vitro pharmacodynamic data for fosfomycin and nitrofurantoin against Pseudomonas Spp., and Acinetobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…In addition, the high resistance pattern observed in NIT (70%) and TR (70%) has also been observed by Chavan et al [71]. A recent study by Chavan et al [71] on 445 strains of P. aeruginosa showed a resistance rate of 97.6% to NIT.…”
Section: Susceptibility Of the P Aeruginosa Strains To Antibioticssupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, the high resistance pattern observed in NIT (70%) and TR (70%) has also been observed by Chavan et al [71]. A recent study by Chavan et al [71] on 445 strains of P. aeruginosa showed a resistance rate of 97.6% to NIT.…”
Section: Susceptibility Of the P Aeruginosa Strains To Antibioticssupporting
confidence: 61%
“…In addition, the high resistance pattern observed in NIT (70%) and TR (70%) has also been observed by Chavan et al [71]. A recent study by Chavan et al [71] on 445 strains of P. aeruginosa showed a resistance rate of 97.6% to NIT. Cunha et al [72], after several years of experience with urinary tract infections, suggested that NIT is active against most common uropathogens, but most Proteus species, Serratia marcescens, and P. aeruginosa are naturally resistant.…”
Section: Susceptibility Of the P Aeruginosa Strains To Antibioticssupporting
confidence: 61%